2020
DOI: 10.1186/s12864-020-07055-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of lncRNA, miRNA and mRNA reveals novel insights into the fertility regulation of large white sows

Abstract: Background Improving sow fertility is extremely important as it can lead to increased reproductive efficiency and thus profitability for swine producers. There are considerable differences in fertility rates among individual animals, but the underlying molecular mechanisms remain unclear. In this study, by using different types of RNA libraries, we investigated the complete transcriptome of ovarian tissue during the luteal (L) and follicular (F) phases of the estrous cycle in Large White pigs with high (H) and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
(116 reference statements)
1
7
0
Order By: Relevance
“…In this study, gilts treated with rpFSH showed higher ovulation number and estrogen concentration, which might contribute to improving the litter size of pigs. Many researches have been reported that lncRNAs could regulated reproduction of pigs (10)(11)(12), but none of these studies have interpreted regulatory networks of lncRNAs for regulation of exogenous hormones on follicular formation in sow production. Therefore, in this study, we performed transcriptome analysis of ovaries in pigs treated with rpFSH by RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, gilts treated with rpFSH showed higher ovulation number and estrogen concentration, which might contribute to improving the litter size of pigs. Many researches have been reported that lncRNAs could regulated reproduction of pigs (10)(11)(12), but none of these studies have interpreted regulatory networks of lncRNAs for regulation of exogenous hormones on follicular formation in sow production. Therefore, in this study, we performed transcriptome analysis of ovaries in pigs treated with rpFSH by RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a number of researches had reported that lncRNAs played important roles in the oogenesis and ovulation in ovaries among different species, including pigs, cattle, mice, and sheep ( 11 , 21 , 32 , 33 ). The present study is the first to report the transcriptome profiling of lncRNAs and mRNA in pig ovaries treated with rpFSH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the coalition analysis between each database is not reported in goat. An integrated analysis of lncRNA, miRNA, and mRNA in ovary at different phases of estrous cycle has been reported to explore the regulation networks in large white sows, and it reveals a novel insight in the regulation of pig fertility [28]. In this study, the databases of miRNA, circRNA, lncRNA, and mRNA in the ovary of Xinong Sannen goat in ES and DS were acquired and analyzed in combination.…”
Section: Introductionmentioning
confidence: 99%